2017
DOI: 10.29356/jmcs.v59i4.81
|View full text |Cite
|
Sign up to set email alerts
|

Free Radicals Induced Oxidative Stress at a Molecular Level: The Current Status, Challenges and Perspectives of Computational Chemistry Based Protocols

Abstract: Oxidative stress is frequently caused by an excess of free radicals and has been associated with a wide variety of health disor-ders. Therefore, finding strategies for scavenging free radicals has be-come an active area of research. This review summarizes, from a physicochemical perspective, relevant strategies to fight oxidative stress via antioxidants, including prevention, deactivation of oxidants, and repair of damaged targets. Different reaction mechanisms in-volved in the chemical protection exerted by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 330 publications
(376 reference statements)
2
87
0
1
Order By: Relevance
“…As the values in Table show, the dominant species at physiological p H are the neutral molecules. However, it has been previously demonstrated that anions can play important roles in reactions mediated by electron transfer, even when they are in a small proportion . That might be the case for NAS, AFMK, 6OHM, and 4OHM, and thus, their anions were also included in the investigation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the values in Table show, the dominant species at physiological p H are the neutral molecules. However, it has been previously demonstrated that anions can play important roles in reactions mediated by electron transfer, even when they are in a small proportion . That might be the case for NAS, AFMK, 6OHM, and 4OHM, and thus, their anions were also included in the investigation.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been previously demonstrated that anions can play important roles in reactions mediated by electron transfer, even when they are in a S C H E M E 2 Structures of melatonin and its metabolites F I G U R E 1 Structure of the three-unit double-stranded DNA (3uDNA) model small proportion. 133,135,136 That might be the case for NAS, AFMK, 6OHM, and 4OHM, and thus, their anions were also included in the investigation. On the other hand, the pKa values for melatonin, c3OHM, and AMK are too high for the anionic species to be chemically relevant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometries and vibrational frequencies were investigated at the M05-2X/6-31+G(d) model chemistries in the gas phase. The HAT and SET mechanisms, which are the most widely accepted antioxidant actions, were evaluated [6,7]. Three intrinsic properties including BDE, adiabatic IE and EA which characterize for the above mechanisms were calculated in the gas phase as follows [8,9].…”
Section: Methodsmentioning
confidence: 99%
“…In these reactions a newly formed radical, which is more stable and less reactive than the previous one, is generated. There are several mechanisms of the antioxidant actions of free radicals: hydrogen atom transfer (HAT), proton coupled electron Transfer (PCET), single electron transfer followed by proton transfer (SET-PT), sequential proton loss electron transfer (SPLET), radical adduct formation (RAF), and sequential proton loss hydrogen atom transfer (SPLHAT) (Klein et al 2007;Litwinienko and Ingold 2007;Galano 2015;Galano et al 2016;Mazzone et al 2016). …”
Section: The Antioxidant Mechanismsmentioning
confidence: 99%